Atmosphere, weather and climate - Barry, Roger G. ([S.l.] : Routledge, 1993)
"Atmosphere, Weather and Climate" provides a thorough introduction to weather processes and climatic conditions. Since the last edition, the recognition of the reality and possible effects of human activities on the environment has revolutionized attitudes to the study of atmosphere and of world climate. Beginning with an extended treatment of atmospheric composition and energy, stressing the heat budget of the earth and the causes of the greenhouse effect, the authors turn to manifestations and circulation of atmospheric moisture, including atmospheric stability and precipitation patterns in space and time. A consideration of atmospheric motion on small to large scales and modelling of general circulation leads to a decision of the structure of air masses, frontal cyclones and weather forecasting on different time scales. The treatment of weather and climate in temperate latitudes begins with studies of Europe and America, extending to the conditions of their polar and sub-tropical margins. Tropical weather and climate are also described through an analysis of the climatic mechanisms of monsoon Asia, Africa and Amazonia, together with the tropical margins of Africa and Australia.
Keywords: atmosphere,weather,climate